New approaches for cement-based prophylactic augmentation of the osteoporotic proximal femur provide enhanced reinforcement as predicted by non-linear finite element simulations. (May 2017) - Varga, Peter; Inzana, Jason A.; Schwiedrzik, Jakob; Zysset, Philippe K.; Gueorguiev, Boyko; Blauth, Michael; Windolf, Markus
Abstract: Background: High incidence and increased mortality related to secondary, contralateral proximal femoral fractures may justify invasive prophylactic augmentation that reinforces the osteoporotic proximal femur to reduce fracture risk. Bone cement-based approaches (femoroplasty) may deliver the required strengthening effect; however, the significant variation in the results of previous studies calls for a systematic analysis and optimization of this method. Our hypothesis was that efficient generalized augmentation strategies can be identified via computational optimization. Methods: This study investigated, by means of finite element analysis, the effect of cement location and volume on the biomechanical properties of fifteen proximal femora in sideways fall. Novel cement cloud locations were developed using the principles of bone remodeling and compared to the "single central" location that was previously reported to be optimal. Findings: The new augmentation strategies provided significantly greater biomechanical benefits compared to the "single central" cement location. Augmenting with approximately 12 ml of cement in the newly identified location achieved increases of 11% in stiffness, 64% in yield force, 156% in yield energy and 59% in maximum force, on average, compared to the non-augmented state. The weaker bones experienced a greater biomechanical benefit from augmentation than stronger bones. The effect of cement volume on the biomechanical properties was approximately linear. Results of the "single central" model showed good agreement with previous experimental studies. Interpretation: These findings indicate enhanced potential of cement-based prophylactic augmentation using the newly developed cementing strategy. Future studies should determine the required level of strengthening and confirm these numerical results experimentally.